The Effect of Interactive Media-Based Clean and Healthy Living Behavior Education on Handwashing Behavior among Early Childhood Children - Fitri Aidani Ulfa Hrp (Jurnal IPTEK Bagi Masyarakat, 2026)
Clean and Healthy Living Behavior (PHBS) is one of the promotive and preventive efforts in improving the health status of early childhood. One of the PHBS indicators that is important to implement from an early age is handwashing with soap. Low handwashing habits in children can increase the risk of infectious diseases such as diarrhea and acute respiratory infections. This study aims to analyze the effectiveness of PHBS education based on interactive media on handwashing behavior in early childhood. The study used a quantitative method with a pre-experimental design through a one-group pretest-posttest design approach. The study population was 25 early childhood children at TKQ Nur Insani and the entire population was sampled using a total sampling technique. The intervention was carried out through PHBS education using animated videos and educational images regarding correct handwashing steps. The research instrument used a handwashing behavior observation sheet based on WHO indicators. Data analysis used the Wilcoxon Signed Rank Test with a significance level of 95%. The results showed an increase in handwashing behavior after being given interactive media-based education. The average value of handwashing behavior before the intervention was 54.20, increasing to 84.60 after the intervention. The statistical test results showed a p-value of 0.000 (<0.05), indicating a significant effect of interactive media-based PHBS education on handwashing behavior in early childhood. This study concluded that PHBS education using interactive media was effective in improving handwashing behavior in early childhood at Nur Insani Kindergarten.